2019
DOI: 10.1371/journal.pone.0212955
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral health conditions and potentially preventable diabetes-related hospitalizations in the United States: Findings from a national sample of commercial claims data

Abstract: Objective To characterize the relationship between potentially preventable hospitalizations (PPHs) for diabetes and behavioral health conditions in commercially insured working-age persons with diabetes in the United States. Research design and methods We retrospectively analyzed medical and pharmacy claims from services rendered between 2011 and 2013 for 229,039 adults with diabetes. Diabetes PPHs were identified using the Agency for Healthcare Research and Quality’s P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 36 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…However, for studies of people with underlying diabetes or cardiovascular disease presenting adjusted hazard ratios, there was little difference between diagnoses of bipolar disorder and schizophrenia. Of the seven studies included in our review which considered schizophrenia alongside other SMI diagnoses, two found patients with schizophrenia were more likely to be hospitalised than other SMI diagnoses [ 31 , 35 ], one found that those with schizophrenia were less likely to be hospitalised [ 36 ], and four found no significant difference [ 37 , 59 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, for studies of people with underlying diabetes or cardiovascular disease presenting adjusted hazard ratios, there was little difference between diagnoses of bipolar disorder and schizophrenia. Of the seven studies included in our review which considered schizophrenia alongside other SMI diagnoses, two found patients with schizophrenia were more likely to be hospitalised than other SMI diagnoses [ 31 , 35 ], one found that those with schizophrenia were less likely to be hospitalised [ 36 ], and four found no significant difference [ 37 , 59 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, we could not control for weight measures such as body mass index (BMI) which is one of the significant predictors for diabetes-related risks 27 , 28 . In addition, healthy behavior such as dietary habits, smoking, drinking, and excise are important determinants particularly for diabetes 29 . We could not include information on the health settings such as a number of primary care providers.…”
Section: Discussionmentioning
confidence: 99%
“…We obtained data from the Clinformatics Data Mart database (Optum), which includes health insurance claims for individuals from all 50 US states receiving private health insurance from a large commercial insurer, with approximately 13 million covered lives annually . The individuals in the database represent about 19% of those with commercial health insurance, and their geographic distribution broadly matches the geographic distribution of the US population .…”
Section: Methodsmentioning
confidence: 99%